Evaluating the Energy Performance of Transparent Photovoltaics for Building Windows in Tropical Climates - Laurentius Kevin Hendinata; Ribka Prilia; Ahmad Ilham Rokhul Fikri; Michael Alfano Suprapto; Nur Abdillah Siddiq (Purnomo Yusgiantoro Center, 2024)
Windows are a critical factor in enhancing energy efficiency in buildings, especially in tropical climates, where they are exposed to high-intensity sunlight. The incorporation of transparent photovoltaics using various PV technologies offers the opportunity for windows to harness solar energy for building purposes. The energy-saving benefits of using transparent photovoltaics have been extensively analyzed in various countries, but there is still a lack of comparative studies focusing on tropical countries. Our study aims to fill this gap by assessing the potential of transparent photovoltaics in enhancing energy efficiency in buildings located in Jakarta, Singapore, Kuala Lumpur, Rio de Janeiro, and Kotoka. We developed an energy consumption model located in a tropical climate, utilizing the EnergyPlus software. The simulation results clearly indicate that integrating photovoltaics into the building is particularly advantageous due to consistent solar radiation and the need for cooling and ventilation, resulting in a substantial up to 59.3% reduction in total energy consumption. As a contribution, our research underscores the potential of transparent photovoltaics to revolutionize building energy efficiency in tropical climates, providing significant energy savings and promoting sustainable building practices. Addressing climate challenges, such as temperature and humidity management, necessitates the utilization of advanced materials and design strategies. Additionally, policy challenges encompass the requirement for favorable policies, incentives, and well-defined guidelines for the installation of PV windows.